People styles at work-- and beyond : making bad relationships good and good relationships better - Bolton, Robert, 1929- (American Management Association, 2009)
Why is it so hard to work well with some people? People Styles at Work ... and Beyond presents a comprehensive, practical, and proven method readers can use to: recognize how they come across to other coworkers read others' body language and behavior to identify the best ways to work with them make small adjustments that will dramatically increase the quality and productivity of their interactions find common ground with different people while retaining their individuality relate less defensively and more effectively--no matter how others act The book reveals the strengths and weaknesses of four different people styles, providing practical techniques that work both on the job and off. Now including all new material on personal relationships, parenting, and more, this is the ultimate guide anyone can use to enhance even the most difficult relationships.